Severity and Impact of rest leg Syndrome on Sleep and its Causative Factors in Pregnant Females of Lahore - Sagheer, Basita; Zahid, Ambreen; Mubeen, Iqra; Jafar, Mahwish; Amin, Fatima; Ali, Muhammad (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Restless legs syndrome is a common musculoskeletal problem which is mostly ignored, undiagnosed and poorly treated, in which individuals complains of dull pain deep in the legs which is frequently felt during inactivity compelling individual to move his leg. The symptoms of rest leg syndrome are mostly severe at night which ultimately causes the sleep disturbance in affected individuals. Objectives: The purpose of the study was to find out the severity and impact of Rest leg syndrome on sleep and its causative factors in pregnant females of Lahore. Methodology: This observational cross study was conducted at University of Lahore from 15 December to 29 December 2015 after the approval of synopsis and data was collected from services hospital, Jinnah Hospital and Sir Ganga ram Hospital, Lahore. By using convenient random sampling technique 384 patients were included the study during 16 weeks. Pregnant females with age between 20- 30 year were included in the study. Subjects with age above 30 presented with Pre-eclampsia, Diabetes, High risk pregnancy, Trauma, Tumor were excluded from the study. Results: Prevalence of leg cramps during pregnancy was found to be 63% it was seen that most of the female experiencing leg cramps were pregnant third time, and 50.8% had bilateral leg cramps, in 54.8% pain was non-radiating and for majority it was of moderate intensity. It was reported by 38.1% of participants that sleep is disturbed due to leg cramps. Conclusion: This study shows leg cramps are common during pregnancy and may be unilateral or bilateral. Results shows high prevalence of leg cramps in pregnant ladies. Furthermore Intensity of leg cramps was moderate for majority of participants.